TRANSPARANSI LAPORAN KEUANGAN SEBAGAI MEDIA KOMUNIKASI DAN INFORMASI BANK PAPUA DALAM KETERBUKAAN INFORMASI PUBLIK - Robinhot Sagala (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
ABSTRACT Bank as a company serving financial services banking sector is regulated and supervised by the Financial Services Authority (OJK). Banking companies are required to carry out all policies established by the Financial Services Authority (OJK), one of which is transparency and publication of the company's performance and capital with the aim of ensuring the availability of information for all stakeholdres. The purpose of the research is to know the transparency of financial statements compiled and presented by Papuan banks to each stakeholder in order to open up public information. The method used in this study is descriptive qualitative research by conducting a literature study of bank papua financial statements in 2019. The results showed that Bank Papua applies the principles of Good Coprporate Governance in running the company, which one of the principles is transparency. The Company provides information that must be provided, must be provided immediately, must be provided at any time and the company's financial statements periodically (monthly, quarterly, yearly) are relevant, reliable, complete, timely and understandble that have been audited by independent auditors. The Company also publishes financial statements through the company's internal and external communication media so that each stakeholder knows the company's performance information.